Predominant Glandular Cholinergic Dysautonomia in Patients With Primary Sjögren's Syndrome. Issue 5 (May 2015) - Imrich, Richard; Alevizos, Ilias; Bebris, Lolita; Goldstein, David S.; Holmes, Courtney S.; Illei, Gabor G.; Nikolov, Nikolay P.
<x xml:space="preserve">Abstract</x> Objective The autonomic nervous system (ANS) modulates exocrine gland function. Available data show poor correlation between the degree of function and destruction of the exocrine glands in primary Sjögren's syndrome (SS), suggesting that other mechanisms, such as autonomic dysfunction, may be important in these patients. The aim of this study was to perform a comprehensive analysis of sympathoneural and sympathetic cholinergic function in well‐characterized patients with primary SS. Methods Twenty‐one patients with primary SS (mean ± SEM age 44.2 ± 2.8 years) and 13 healthy control subjects (mean ± SEM age 50.8 ± 1.9 years) were assessed during orthostasis and intravenous injection of edrophonium (10 mg). The postganglionic sympathetic cholinergic system was evaluated by assessing sweat production by means of the Quantitative Sudomotor Axon Reflex Test (QSART). Tests of gastric empting were used to assess the gastrointestinal ANS in primary SS patients. Results The velocity index and the acceleration index were significantly higher (P < 0.05) in patients with primary SS as compared to controls, both before and during the orthostatic and edrophonium tests. Findings of other hemodynamic and neurochemical parameters did not differ between primary SS patients and controls during the orthostasis and edrophonium test; however, the edrophonium‐induced saliva increment was lower in primary SS patients (P = 0.002). Abnormally low sweat production was found in 4 primary SS patients but in none of the controls, as determined by the QSART. Gastric empting was delayed in 53% of primary SS patients. Conclusion We observed subtle differences in several ANS domains, including the gastrointestinal and sympathocholinergic systems, suggesting the presence of a complex ANS dysfunction in primary SS. The impact was greatest on the exocrine glands, with subtle differences in the cardiac parasympathetic function that were independent of glandular inflammation and atrophy, suggesting an alternative mechanism of disease pathogenesis in primary SS.